PENGANTAR HUKUM PAJAK SERTA ATURAN DAN REGULASI YANG BERLAKU - Rizki Khoiril Waladi Siahaan; Dea Salsabila (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to examine the role of tax law in the Indonesian tax system, with a focus on its fundamental ideas, purposes, place in the legal system, and relevant laws and regulations. Using secondary data gathered from a literature review, normative legal research with a legislative and conceptual perspective is the methodology employed. According to the study's findings, tax legislation serves as both the legal basis for tax collection and a tool for promoting equity, legal certainty, and taxpayer compliance. Although tax law is a part of public law in Indonesia, it is intimately related to criminal and civil law. From the constitution to technical rules like Ministerial Decrees (PMK) and Director General's Decrees (Perdirjen), tax laws in Indonesia are organised hierarchically. Additionally, taxpayers are protected by legal remedies including objections and appeals. Tax law has also been demonstrated to have a major impact on taxpayer compliance levels through greater public legal awareness, law enforcement, and regulatory clarity